Stakeholder Engagement in Competency Framework Development in Health Professions: A Systematic Review - Lepre, Breanna; Palermo, Claire; Mansfield, Kylie J.; Beck, Eleanor J. (Frontiers in Medicine, 2021)
Competency framework development in health professions has downstream implications for all relevant stakeholders, from the professionals themselves, to organisations, and most importantly end users of services. However, there is little guidance related to what stakeholders might be involved in the competency development process, and when. This review aimed to systematically review literature related to competency framework development methodology in health, to identify the breadth and purpose of key stakeholders commonly involved in the process. Studies were identified using five electronic databases (MEDLINE, PubMed, CINAHL, EMBASE, and ERIC) and a search of websites of organisations involved in curriculum or regulation using keywords related to competency frameworks. The total yield from all databases was 10,625 results, with 73 articles included in the final review. Most articles were from Australia (30%) and were conducted in the nursing (34%) profession. Unsurprisingly, practitioners (86%) and academics (75%) were typically engaged as stakeholders in competency framework development. While many competency frameworks were described as patient-focused, only 14 (19%) studies elected to include service users as stakeholders. Similarly, despite the multi-disciplinary focus described in some frameworks, only nine (12%) studies involved practitioners from other professions. Limiting the conceptualisation of competence to that determined by members of the profession itself may not provide the depth of insight required to capture the complexity of healthcare and address the needs of important stakeholder groups. Future methodology should attempt to engage a variety of relevant stakeholders such as external health professions and the community to match professional education to health service demands. Systematic Review Registration:https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=128350